2018
DOI: 10.1186/s40249-018-0427-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and molecular characterization of diarrheagenic Escherichia coli and non-typhoidal Salmonella strains isolated from infections in Southwest China

Abstract: BackgroundBacterial diarrhea is one of the most common causes for medical consultations, mortality and morbidity in the world. Diarrheagenic Escherichia coli (DEC) and non-typhoidal Salmonella (NTS) are major intestinal pathogens in developing countries, and the indiscriminate use of antibiotics has greatly contributed to resistant strains. Hence, the aim of the present study is to identify the antimicrobial resistance patterns and the molecular characteristics of DEC and NTS in southwest, China.Methods1121 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 47 publications
2
24
5
Order By: Relevance
“…In our study, S. enteritidis (29.6%) was the second common subtype identified among the NTS isolated from stool samples. A study from Southwest China reported S. enteritidis as the most predominant subtype identified, however with a much lower rate (1.87%) than that reported in our study (27). Another study from Venezuela reported that S. enteritidis (48.7%) as the predominant serovar followed by S. typhimurium (37.8%) which is contrary to our result where S. typhimurium was the most common subtype followed by S. enteritidis (25).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In our study, S. enteritidis (29.6%) was the second common subtype identified among the NTS isolated from stool samples. A study from Southwest China reported S. enteritidis as the most predominant subtype identified, however with a much lower rate (1.87%) than that reported in our study (27). Another study from Venezuela reported that S. enteritidis (48.7%) as the predominant serovar followed by S. typhimurium (37.8%) which is contrary to our result where S. typhimurium was the most common subtype followed by S. enteritidis (25).…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the prevalence of NTS was 10.1% and iNTS was 9.4%. A study from Northwest China reported NTS prevalence at a rate of 3.75% from the diarrheal patients and 0.31% from the non-diarrheal patients, which was much lower than that reported in our study (27). In contrast, studies from the US (42%) and Shangai (17.2%) reported NTS as the leading cause of bacterial enteric illness, which was much higher than that reported in our study (15,28).…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations